1998
DOI: 10.1074/jbc.273.32.19965
|View full text |Cite
|
Sign up to set email alerts
|

ATP-stimulated Activation of the Mitogen-activated Protein Kinases through Ionotrophic P2X2 Purinoreceptors in PC12 Cells

Abstract: Extracellular purine nucleotides elicit a diverse range of biological responses through binding to specific cell surface receptors. The ionotrophic P2X subclass of purinoreceptors respond to ATP by stimulation of calcium ion permeability; however, it is unknown how P2X purinoreceptor activation is linked to intracellular signaling pathways. We report that stimulation of PC12 cells with ATP results in the activation of the mitogen-activated protein (MAP) kinases ERK1 and ERK2 and was wholly dependent upon extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 30 publications
4
46
2
Order By: Relevance
“…Such ionic perturbations are sufficient to trigger activation of a number of intracellular signaling molecules, including MAP kinases [74]. It has been shown that ATP can induce Ca 2+ -dependent phosphorylation of ERK in PC12 cells and fetal astrocytes [74,75] and of JNK in mouse macrophages [76].…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…Such ionic perturbations are sufficient to trigger activation of a number of intracellular signaling molecules, including MAP kinases [74]. It has been shown that ATP can induce Ca 2+ -dependent phosphorylation of ERK in PC12 cells and fetal astrocytes [74,75] and of JNK in mouse macrophages [76].…”
Section: Intracellular Signalingmentioning
confidence: 99%
“…These effects might be due to each MAPK phosphorylating a different site among the several consensus sites on cPLA 2 or to the integration of the phosphorylation of both MAPK by an upstream enzyme, which then activates cPLA 2 , as in cardiomyocytes (34). Finally, calcium chelation did not prevent the activation of ERK1/2 and p38 MAPKs by ATP; therefore, the activation of the MAPKs is not due to increased intracellular calcium, as in HEK-293 cells (44) or in response to ATP in PC12 cells (45). Thus, ATP activates three distinct intracellular signaling pathways that act independently and simultaneously (Fig.…”
Section: Fig 5 Effect Of Atp On Erk and P38 Mapks Phosphorylationmentioning
confidence: 99%
“…PC12 cells are known to possess both P1 and P2 receptors that are highly sensitive to Ado and ATP, respectively. [4][5][6][7][8][9][10][11] Among the subtypes of P1 receptors, PC12 cells have been shown to possess the A2a and A2b but not A1 or A3 Ado receptors on the basis of studies using the radioligand binding technique, 22,23) elevation of cAMP accumulation, 24,25) and reverse-transcriptase polymerase chain reaction. 6,[23][24][25] In PC12 cells, the nonselective A1/A2 agonist NECA was reported to result in greater accumulation of cAMP than did the A2a-selective agonist CGS 21680.…”
Section: Metabolism Of Extracellular Ado and Atp By Pc12mentioning
confidence: 99%
“…1,3) A number of cellular responses induced by Ado [4][5][6] and ATP [7][8][9][10][11] in rat pheochromocytoma PC12 cells, a neuronal model, have been demonstrated to be mediated mainly through P1 and P2 receptors. PC12 cells are known to have A2a and A2b but not A1 or A3 receptors among the P1 receptor subtypes, and P2X 2 , P2Y 1 , and P2Y 2 among the P2 receptor subtypes.…”
mentioning
confidence: 99%